Improving the Quality of Academic Services at Ibrahimy University - Syahrul Ibad (Universitas Sebelas Maret, 2021)
This research is based on the issue of Government Regulation of the Republic of Indonesia Number 5 of 1980 concerning Duties and Functions of Universities which states that the main task of universities/institutes is to provide education and teaching in universities based on the culture of the Indonesian nation. This is done in scientifically involving education and teaching, research, and community service in accordance with the applicable laws and regulations. The research focuses on the theory of public service quality through how to improve the quality of academic administration services at Ibrahimy University. The research method used was qualitative research with the methods of describing, reconstructing, and analyzing the result of research. The results show that the improvement of academic service quality in Ibrahimy University was carried out in the following ways: Firstly, planning for academic services was marked by the formation of a team, data collection, formulation of strategic plans, discussion of strategic plans, and socialization; secondly, the organization of academic services is marked by the formation of organizational units, placement of personnel, and arrangement of quality documents; thirdly, the implementation of academic services is marked by the existence of learning services but not optimal, guidance services and library services that are already optimal; and fourthly, the supervision of academic services is carried out in the form of evaluating the performance of lecturers by the team, especially in learning.